Cost and utilization outcomes of opioid-dependence treatments. - Baser, Onur; Chalk, Mady; Fiellin, David A; Gastfriend, David R (The American journal of managed care, 2011)
To evaluate the healthcare costs associated with treatment of opioid-dependence disorder with medications versus no medication, and with the 4 agents approved by the US Food and Drug Administration (FDA).
Keywords: Adult; Chi-Square Distribution; Female; Health Care Costs; Health Services; Humans; Inpatients; Insurance Claim Review; Male; Naltrexone; Narcotic Antagonists; Opioid-Related Disorders; Outpatients; Retrospective Studies; Statistics, Nonparametric; Treatment Outcome; United States